A New Method of Haemorrhagic Stroke Detection Via Deep Magnetic Induction Tomography - Lv, Yi; Luo, Haijun (Frontiers in Neuroscience, 2021)
Haemorrhage imaging is one of the most common applications of magnetic induction tomography (MIT). Depth and focusing are the most important issues that need to be solved for this application. Transcranial magnetic stimulation (TMS) is a technique belonging to the deep brain stimulation (DBS) field, which aims at overcoming human diseases such as depression. TMS coils, namely, circular, figure-8, and H–coils, play an important role in TMS. Among these, H-coils individually focus on the issues of depth and focusing. MIT and TMS mechanisms are similar. Herein, for the first time, improved TMS coils, including figure-8 and H-coils, are applied as MIT excitation coils to study the possibility of achieving focusing and deep detection through MIT. In addition, the configurations of the detection coils are varied to analyse their influence and determine the optimal coils array. Finally, MIT is used to detect haemorrhagic stroke occurring in humans, and the application of deep MIT to the haemorrhagic stroke problem is experimentally explored. Results show that improved H-coils are the most focusing and deep among the various coils that enable the detection of deep strokes through MIT. Although the detecting depth of the figure-8 coil is weaker, its surface signal is the best. The deep MIT technique can be applied to haemorrhagic detection, providing a critical base for deeper research.